Formation and circulation of Ice Shelf Water in the Weddell and Ross seas - Nøst, Ole Anders (University of Bergen, 1995)
Keywords: Rosshavet; Sørishavet; Weddellhavet; geofysikk; oseanografi

Distribution of Water Masses on the Continental Shelf in the Southern Weddell Sea - Gammelsrød, Tor; Foldvik, Arne; Nøst, Ole Anders; Foldvik, Ø.; Anderson, Leif G.; Fogelqvist, Elisabet; Olsson, K. Anders; Tanhua, Toste; Jones, Elizabeth Peter; Østerhus, Svein (The Polar Oceans and Their Role in Shaping the Global Environment, 1994)
Water properties on the continental shelf in the southern Weddell Sea observed during NARP 92/93 are presented. The station distribution includes a section close to the floating ice shelf from the Filchner Depression to the Antarctic Peninsula. Temperature, salinity, oxygen, silicate, CFC-ll and CFC-12 distributions are shown. Melting under the ice shelves, circulation systems, residence times, sediment/water interactions and bottom water formation are discussed. Ice Shelf Water (ISW), which is formed by cooling and melting below the floating ice shelf, seems to be about 10 years older than its parent water mass, which indicates the residence time below the ice shelf. The average melting rate below the Filchner Ronne ice shelf, based on the volume flux of ISW in the Filchner Depression is estimated to be 0.1 m/year. Compared with earlier observations considerable changes were found in the water characteristics and distribution: The temperature of the Weddell Deep Water has increased 0.7°C since 1977. Western Shelf Water, usually dominating the bottom layers in the Filchner Depression and on the Berkner Shelf, was found only in the Ronne Depression.
Keywords: NARP 1992/93; Sørishavet; Weddellhavet; geofysikk; oseanografi

Bunnvannsstrømmer på kontinentalskråningen i Weddellhavet - Nordlund, Nina (Universitetet i Bergen, 1992)
Keywords: Sørishavet; Weddellhavet; bunnvann; geofysikk; havstrømmer; oseanografi

En modell for sirkulasjonen under isshelfene i Weddelhavet og Rosshavet - Nøst, Ole Anders (O. A. Nøst, 1992)
Keywords: Rosshavet; Sørishavet; Weddellhavet; geofysikk; oseanografi

Crustal development: Weddel Sea - Ross Sea region. Evolution of the Gondwana plate boundary in the Weddel Sea area - Kristoffersen, Yngve; Hinz, Karl (Geological evolution of Antarctica : proceedings of the Fifth International Symposium on Antarctic Earth Sciences, held at Robinson College, Cambridge, 23-28 August 1987, 1991)
Keywords: Antarktis; Weddellhavet; geofysikk; geologi; seismologi; tektonikk

Alternate Carbon Pathways at Lower Trophic Levels in the Antarctic Food Web - Hewes, Christopher D; Holm-Hansen, Osmund; Sakshaug, Egil (Antarctic Nutrient Cycles and Food Webs, 1985)
Keywords: Sørishavet; Weddellhavet; diatomeer; fytoplankton; krill; marin biologi; oseanografi; plankton

Glacial erosion and morphology of the eastern and southeastern Weddell Sea shelf - Elverhøi, Anders; Maisey, George (Cambridge University Press, 1983)
Keywords: NARE ekspedisjoner; Sørishavet; Weddellhavet; geologi; glasiologi

Marine geophysical research in the Weddell Sea during the Norwegian Antarctic research expedition of 1976-77 - Fossum, Bjørn A.; Maisey, Georg H.; Torsen, Hans Olav (Antarctic geoscience : Symposium on Antarctic Geology and Geophysics, Madison, Wisconsin, U.S.A., August 22-27, 1977, 1982)
Keywords: NARE 1976/77; Sørishavet; Weddellhavet; ekspedisjoner; geologi; marin geofysikk

Seismic reconnaissance survey in the Weddell Sea - Haugland, Kristen (Symposium on Antarctic Geology and Geophysics, 1982)
Keywords: NARE 1976/77; Sørishavet; Weddellhavet; ekspedisjoner; havbunnen; sedimentologi; seismologi

Iceberg response to sea state - Orheim, Olav; Wadhams, Peter; Kristensen, Monica (Iceberg research, 1982)
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; ekspedisjoner; forskning; isberg; isfjell; målinger

Sea bed feauters in the Blåenga area, Weddell Sea, Antarctica - Lien, Reidar (Université Laval, 1981)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; geologi; havbunnen; kongress; oseanografi; symposium

Model for submarine glacial deposition - Orheim, Olav; Elverhøi, Anders (Annals of Glaciology, 1981)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; havbunnen; oseanografi

Measurements of oscillations and flexure of icebergs - Foldvik, Arne; Gammelsrød, Tor; Gjessing, Yngvar (Annals of Glaciology, 1980)
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; glasiologi; havis; is; isbreer

Physical characteristics and life expectancy of tabular Antarctic icebergs - Orheim, Olav (Annals of Glaciology, 1980)
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; glasiologi; isberg; isfjell; isfront; isshelf; kalving; stratigrafi

Verdens kaldeste sjøvann - Foldvik, Arne; Gade, Herman G (Naturen, 1978)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; observasjoner; oseanografi; sjøvann; vannmasser

Hvor driver de antarktiske isfjellene? - Vinje, Torgny E (Naturen, 1978)
Keywords: Sørishavet; Weddellhavet; drivis; forskning; havis; havstrømmer; isberg; isdrift; issfjell; oseanografi; sjøis; sjøvann

Bottom currents in the Weddel Sea. Results of long time curretmeter moorings at 74°S, 40°W, during IWSOE 1968-1973 - Foldvik, Arne; Kvinge, Thor (University of Bergen, 1974)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; oseanografi

Theories of bottom water formation, recent investigations in the Weddell Sea and the effects of super cooling by the ice cap - Mosby, Håkon (Japan Society for the Promotion of Science, 1971)
Keywords: Sørishavet; Weddellhavet; bunnvannet; kongress; oseanografi; sjøvann

Cruise reports. International Weddell Sea Oceanographic Expedition : conducted onboard USCGC GLACIER (WAGB-4) - Kvinge, Thor (University of Bergen, 1970)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; fysisk oseanografi; geofysikk; oseanografi

International Weddell Sea oceanographic expedition : position and weather journal USCGC Glacier - Kvinge, Thor (University of Bergen, 1970)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; fysisk oseanografi; meteorologi; oseanografi

Remarks on processes pertinent to the formation of bottom water in the Weddel Sea - Foldvik, Arne; Kvinge, Thor (University of Bergen, 1969)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; oseanografi

IWSOE - 69 : position and weather journal USCGC "Glacier" - Kvinge, Thor (University of Bergen, 1969)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; fysisk oseanografi; meteorologi; oseanografi

Technical report on project to measure currents related to the formation of Antarctic bottom water in the Weddell Sea : United States Antarctic Research Program : International Weddell Sea Oceanographic Expedition, 1968 : conducted onboard USCGC glacier (WAGB-4) - Kvinge, Thor (University of Bergen, 1968)
Keywords: AABW; Sørishavet; Weddellhavet; bunnvannet; ekspedisjoner; isberg; observasjoner; oseanografi; sjøvann

Bottom water formation - Mosby, Håkon (SCAR/SCOR/IAPO/IUBS, 1966)
Keywords: Sørishavet; Weddellhavet; bunnvann; bunnvannsformasjoner; havstrømmer; oseanografi; sjøvann

South Atlantic bottom water - Mosby, Håkon (Scientific Committee on Antarctic Research, 1966)
Keywords: Sørishavet; Weddellhavet; bunnvann; bunnvannsformasjoner; havstrømmer; oseanografi; sjøvann

On the conditions for the production of plankton in the sea - Gran, Haaken Hasberg (Conseil Perm. Internat. pour I'Explor. de la Mer. Rapp. et Proces-Verb., 1931)
Keywords: Sørishavet; Weddellhavet; krill; marin biologi; oseanografi; plankton; zooplankton